Pemanfaatan AI dalam Media Pembelajaran dan PPDB di Yayasan Miftahul Huda Grobogan - Ramadhani, Lingga Kurnia; Ariwibowo, Bayu; Abdillah, Fuad; Budiyanto, Budiyanto; Widyaningrum, Bajeng Nurul (CV. Ulil Albab Corp, 2025)
Workshop